Comparative capacity of global mining regions to transition to a post-mining future. (September 2022) - Everingham, Jo-Anne; Svobodova, Kamila; Lèbre, Éléonore; Owen, John R.; Worden, Sandy
Highlights: Demonstrates a data-driven process to locate mining regions globally. Multi-scale, multi-dimensional analysis of complexities associated with the closure of mines. A framework to evaluate regional capacity to manage transition to a sustainable post-mine future. Analyses three tiers of mining regions with varying conditions for transition to closure. A high-level global comparison of how regions might cope with their sustainability transitions. Abstract: This paper focuses on the ability of regions where mining is concentrated to adapt to closure given the regional assets and the complexities of their association with declining production of various commodities. We propose a conceptual framework to examine the relative capacity of global regions to transition and prosper post-mining by analysing contextual factors and characterising the mining footprint in the regions. Public sources of geo-locatable data are used to define and locate mining regions in transition and to assess the interacting mining and contextual factors that enable or constrain their capacity to transition. The data-driven examination illuminates the comparative capacity of global regions confronting the challenge of mine closure. It engages with themes from regional studies, mine closure and transition studies to consider multidimensional aspects of regional transition. Graphical abstract: Image, graphical abstract